2023
DOI: 10.3390/biology12020258
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Bacterial Community of Mustard Pickle Products and Their Microbial and Chemical Qualities

Abstract: We assessed the microbial and chemical qualities and microbiomes of 14 mustard pickle products coded sequentially from A to N and sold in traditional Taiwanese markets. The results showed that the aerobic plate count and lactic acid bacteria count of commercially available mustard pickle products were 2.18–4.01 and <1.0–3.77 log CFU/g, respectively. Moreover, no coliform bacteria, Escherichia coli, Staphylococcus aureus, Salmonella spp., or Listeria monocytogenes were detected in any of the samples. Analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…In the present study, there was no Salmonella detected in pickled cucumber (Table 2). Similar result was showen by Chien et al (2023) [32] that revealed that no Salmonella spp. was detected in Pickles.…”
Section: Discussionsupporting
confidence: 84%
“…In the present study, there was no Salmonella detected in pickled cucumber (Table 2). Similar result was showen by Chien et al (2023) [32] that revealed that no Salmonella spp. was detected in Pickles.…”
Section: Discussionsupporting
confidence: 84%
“…Biogenic amines are toxic and may cause allergic reactions in specific individuals [ 35 ]. In the meantime, fermented vegetables may be more prone to microbial contamination during the processing stage if the production process is not performed correctly [ 36 ]. Consuming fermented vegetables infected with pathogenic microorganisms poses a risk of foodborne pathogen infection since fermented vegetables are rarely exposed to thermal sterilization before being consumed.…”
Section: Introductionmentioning
confidence: 99%